Metabotropic glutamate 5 receptor in the infralimbic cortex contributes to descending pain facilitation in healthy and arthritic animals. (15th January 2016) - David-Pereira, A.; Puga, S.; Gonçalves, S.; Amorim, D.; Silva, C.; Pertovaara, A.; Almeida, A.; Pinto-Ribeiro, F.
Highlights: The infralimbic and prelimbic cortices tonically promote spinal antinociception. Glutamate in the infralimbic cortex enhances behavioral hyperalgesia. mGluR5 mediates infralimbic-induced hyperalgesia in control and monoarthritic rats. Selective inhibition of mGluR5 prevents IL-induced pronociception. Abstract: The involvement of the prefrontal cortex in pain processing has been recently addressed. We studied the role of the infralimbic cortex (IL) and group I metabotropic glutamate receptors (mGluRs) in descending modulation of nociception in control and monoarthritic (ARTH) conditions. Nociception was assessed using heat-induced paw withdrawal while drugs were microinjected in the IL of rats. Local anesthesia of the IL or the adjacent prelimbic cortex (PL) facilitated nociception, indicating that IL and PL are tonically promoting spinal antinociception. Phasic activation with glutamate (GLU) revealed opposing roles of the PL and IL; GLU in the PL had a fast antinociceptive action, while in the IL it had a slow onset pronociceptive action. IL administration of a local anesthetic or GLU produced identical results in ARTH and control animals. An mGluR5 agonist in the IL induced a pronociceptive effect in both groups, while mGluR5 antagonists had no effect in controls but induced antinociception in ARTH rats. Activation of the IL mGluR1 (through co-administration of mGluR1/5 agonist and mGluR5 antagonist) did not alter nociception in controls but induced antinociception in ARTH animals. IL administration of an mGluR1 antagonist failed to alter nociception in either experimental group. Finally, mGluR5 but not mGluR1 antagonists blocked the pronociceptive action of GLU in both groups. The results indicate that IL contributes to descending modulation of nociception. mGluR5 in the IL enhance nociception in healthy control and monoarthritic animals, an effect that is tonic in ARTH. Moreover, activation of IL mGluR1s attenuates nociception following the development of monoarthritis.